Vertically-Oriented Graphene: PECVD Synthesis and Applications - Junhong, Chen (Springer, 2016)
This book introduces the basic concepts, synthesis techniques, and applications of vertically-oriented graphene. The authors detail emerging applications of vertically-oriented graphene such as field emitters, atmospheric nanoscale corona discharges, gas sensors and biosensors, supercapacitors, lithium-ion batteries, fuel cells (catalyst supports) and electrochemical transducers. They offer a perspective on current challenges to enabling commercial applications of vertically-oriented graphene.